Etiology of Tendency Toward Using Cannabis: A Qualitative Study of the Lived Experiences of Teenager’s Consumers - Soodabeh Rostami; Atousa Kalantar Hormozi; Mohammad Asgari; Ezzatollah Kordmirza Nikoozadeh (Taṣvīr-i salāmat)
Background. In recent years, the use of cannabis among teenagers has been on the rise, being considered one of the health-social challenges of the country. The present study aimed at providing a better understanding of the causes of teenagers’ tendency to use cannabis by looking at the life experiences of those who consume it. Methods. This qualitative study utilized a descriptive phenomenological method, conducting in-depth, semi-structured interviews with 11 teenagers aged 17-20 years old who used cannabis at least once a week in Mashhad city (Iran) in 2022. Participants were selected by convenience and purposive sampling methods. Data collection continued until reaching the theoretical saturation stage, and the collected data were analyzed by the coding method. Results. The analysis of the participants’ experiences led to the identification of 136 primary codes, 30 sub-categories, 11 main categories, and 2 core categories. The core categories included intrapersonal components and interpersonal-extrapersonal components in relation to teenagers’ tendency to use cannabis. Main categories included cognitive distortion regarding the effects of cannabis, low mood frustration, lack of a specific work plan, having an unstable personality, unawareness of the harmful nature of cannabis, usage to cope with emotional problems, usage to cope with parental conflicts, peer influence on usage, justification of usage by modeling after prominent figures, and accessibility (easy access) leading to increased usage. Conclusion. Exploring the experiences and views of adolescents who consume cannabis in intrapersonal, interpersonal, and extrapersonal domains provided more knowledge about different indicators of cannabis consumption among teenagers. Considering the obtained components can serve as a helpful first step in developing efficient intervention measures according to the identified needs.